2010
DOI: 10.1111/j.1465-7287.2010.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Relationship Between Productivity and Farm Size: The Case of China

Abstract: In developing agricultures, past research has suggested an inverse relationship between farm productivity and size. The raw data from China show such an inverse relationship. However, the inverse relationship disappears after we instrument for land area using the fact that one of the objectives of the land allocation process in rural China is to ensure local households to meet their nutritional needs. The empirical inverse relationship is likely due to the failure to account for the unobserved land quality tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
0
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 52 publications
7
38
0
13
Order By: Relevance
“…12 Our tests closely follow Chen, Huffman and Rozelle (2011). 13 Rather than being a complementary good to learning from neighbors, the education level may be a substitute.…”
Section: Discussionmentioning
confidence: 84%
“…12 Our tests closely follow Chen, Huffman and Rozelle (2011). 13 Rather than being a complementary good to learning from neighbors, the education level may be a substitute.…”
Section: Discussionmentioning
confidence: 84%
“…Chen et al (2011) find that the inverse relationship disappears in farms in China once the land quality is taken into account. On the other hand, Barret et al (2010) using data from Madagascar reject that the inverse relationship is explained by soil quality.…”
Section: Farm Size and Productivity: An Inverse Relationship?mentioning
confidence: 88%
“…Following the literature examining the inverse relationship between farm size and productivity (Assuncao and Ghatak 2003;Deininger and Byerlee 2012), Chen et al (2010) examine the relationship between farm size and productivity in China using farm-level household survey data between 1995 and 1999. Their study found that total farm output in China declined with cultivated land area, and this could be attributed to local administrative land distribution policies, uneven off-farm work opportunities and heterogeneity in land quality.…”
Section: Agricultural Mechanisation and Contracting Capital Servicesmentioning
confidence: 99%